2009
DOI: 10.1007/s11768-009-8005-6
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic moving average control approach to cylinder pressure and its experimental validation

Abstract: Cyclic variability is a factor adversely affecting engine performance. In this paper a cyclic moving average regulation approach to cylinder pressure at top dead center (TDC) is proposed, where the ignition time is adopted as the control input. The dynamics from ignition time to the moving average index is described by ARMA model. With this model, a one-step ahead prediction-based minimum variance controller (MVC) is developed for regulation. The performance of the proposed controller is illustrated by experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…From the experiments, even when the offset is eliminated, y k has a high noise level. To alleviate the noise effect, a new index generated from the moving average method [14, 15] is employed for modelling. However, the horizon of the moving average method is determined experimentally.…”
Section: Control Schemesmentioning
confidence: 99%
“…From the experiments, even when the offset is eliminated, y k has a high noise level. To alleviate the noise effect, a new index generated from the moving average method [14, 15] is employed for modelling. However, the horizon of the moving average method is determined experimentally.…”
Section: Control Schemesmentioning
confidence: 99%
“…Li et al used ARMA model for the dynamics from spark timing to four-cycle moving average of inecylinder pressure at TDC. The results showed that the control scheme could obtain reliable effect for the inecylinder pressure at TDC regulation when engine worked under different fuel injection strategies, load changing and throttle opening disturbances [25].…”
Section: Introductionmentioning
confidence: 98%
“…The possibility of sensing the air-fuel ratio of spark ignition (SI) engines leads to the development of effective air-fuel ratio control strategies. There are many researches that have been presented about in-cylinder pressure applications for internal combustion engines control and analysis [1][2][3]. For the air-fuel ratio estimation based on in-cylinder pressure measurement, there are many approaches that have been applied, for example [4].In previous work [5], we have been introduced the air-fuel ratio model based on in-cylinder pressure measurement for calculation of the static air-fuel ratio of the SI engine.…”
Section: Introductionmentioning
confidence: 99%